Niche segregation and genetic structure of Campylobacter jejuni populations from wild and agricultural host species - SAMUEL K. SHEPPARD; FRANCES M. COLLES; NOEL D. McCARTHY; NORVAL J. C. STRACHAN; IAIN D. OGDEN; KEN J. FORBES; JOHN F. DALLAS; MARTIN C. J. MAIDEN (Molecular Ecology, 2011)
Bacterial populations can display high levels of genetic structuring but the forces that influence this are incompletely understood. Here, by combining modelling approaches with multilocus sequence data for the zoonotic pathogen Campylobacter, we investigated how ecological factors such as niche (host) separation relate to population structure. We analysed seven housekeeping genes from published C. jejuni and C. coli isolate collections from a range of food and wild animal sources as well as abiotic environments. By reconstructing genetic structure and the patterns of ancestry, we quantified C. jejuni host association, inferred ancestral populations, investigated genetic admixture in different hosts and determined the host origin of recombinant C. jejuni alleles found in hybrid C. coli lineages. Phylogenetically distinct C. jejuni lineages were associated with phylogenetically distinct wild birds. However, in the farm environment, phylogenetically distant host animals shared several C. jejuni lineages that could not be segregated according to host origin using these analyses. Furthermore, of the introgressed C. jejuni alleles found in C. coli lineages, 73% were attributed to genotypes associated with food animals. Our results are consistent with an evolutionary scenario where distinct Campylobacter lineages are associated with different host species but the ecological factors that maintain this are different in domestic animals such that phylogenetically distant animals can harbour closely related strains.